Two-leg module of a six-legged robot - Tienzo, Julie-marie M. (2004)
The project is a two-leg module which comprises a pair of opposite legs, Each leg bears two degrees of freedom. A joint consists of a set of two servo motors. In every set, one motor is used to control the sweep of the leg, and the other to control the lifting action of the leg. To demonstrate the movement of the legs, a hybrid robot is created. Wheels are attached to the module in order to comply with required ground contacts for static stability.